Valuasi Startup Teampal.Id Menggunakan The Dave Berkus Method - Kasyana, I Putu; Putri, I Gst Agung Pramesti Dwi; Dewi, Putri Anugrah Cahya (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
Startups have gained popularity among young entrepreneurs in Indonesia, inspired by successful local Startups such as Gojek, Shopee, and Tokopedia. However, many Startups face challenges and failures. Teampal.id, a Startup based in Bali, is an example of a growing Startup. It provides livestock farming packages and cultivation development, involving investors from various sectors of society. To scale up their business, Teampal.id requires sufficient funding. Therefore, this research aims to calculate the valuation of Teampal.id Startup using The Dave Berkus Method. This Method evaluates the overall value of a Startup based on five key elements, including the Startup's core idea, Prototype/product, team management, strategic relationships, and sales. The findings of this research are expected to contribute to Teampal.id in addressing valuation challenges and acquiring the necessary funds for their business growth. Additionally, it will provide insights and guidance for other Startups in the fundraising process.